Zoë bakes cakes ebook Everything you need to know to make your favorite layers, bundts, loaves, and more [a baking book]. - François, Zoë (2021)
IACP AWARD WINNER • The expert baker and bestselling author behind the Magnolia Network original series Zoë Bakes explores her favorite dessert—cakes!—with more than 85 recipes to create flavorful and beautiful layers, loafs, Bundts, and more.   “Zoë’s relentless curiosity has made her an artist in the truest sense of the word.”—Joanna Gaines, co-founder of Magnolia NAMED ONE OF THE BEST COOKBOOKS OF THE YEAR BY TIME OUT   Cake is the ultimate symbol of celebration, used to mark birthdays, weddings, or even just a Tuesday night. In Zoë Bakes Cakes , bestselling author and expert baker Zoë François demystifies the craft of cakes through more than eighty-five simple and straightforward recipes. Discover treats such as Coconut–Candy Bar Cake, Apple Cake with Honey-Bourbon Glaze, and decadent Chocolate Devil’s Food Cake. With step-by-step photo guides that break down baking fundamentals—like creaming butter and sugar—and Zoë’s expert knowledge to guide you, anyone can make these delightful creations.    Featuring everything from Bundt cakes and loaves to a beautifully layered wedding confection, Zoë shows you how to celebrate any occasion, big or small, with delicious homemade cake.